The Role Of Social Media Use In Shaping Digital Literacy And Ipas Learning Achievement: A Mediation Model In Elementary Education - Muhamad Andriansah Purba; Jajang Hendar Hendrawan; Neneng Tripuspita (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study examines the role of social media use in shaping digital literacy and its impact on IPAS (Integrated Science and Social Studies) learning achievement among elementary school students. It also investigates the mediating role of digital literacy in the relationship between social media use and academic performance. A quantitative explanatory design was employed involving 30 fifth-grade students from SD Negeri Rawasirna, Cianjur, Indonesia. Data were collected using a validated Likert-scale questionnaire and students’ academic scores, and analyzed through simple and multiple regression, as well as mediation analysis using the Sobel test. The findings reveal that social media use significantly influences digital literacy (p < .001), but does not directly affect IPAS learning achievement (p > .05). In contrast, digital literacy has a significant positive effect on academic achievement (p < .05) and mediates the relationship between social media use and learning outcomes. These results indicate the presence of a digital-academic gap, where digital engagement enhances competencies but does not automatically translate into academic performance. This study highlights the importance of integrating digital literacy into structured pedagogical practices, particularly in IPAS learning contexts. The findings contribute to the limited empirical evidence on digital literacy mediation in elementary education in Indonesia.